A profile of the United States toy industry : serious fun - Byrne, Christopher (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
The toy industry is one of the most consistently misunderstood sectors of American business, comprising a wide range of businesses under one banner-entertainment, commodities, fashion and licensing-that each behave differently. The broad and diverse market is constantly changing, with more than 40 percent of products new each year. Today, it is a mix of approximately 600 publicly and privately held companies. Currently about $22 billion per year at wholesale for traditional toys, the size of the United States toy industry has remained relatively constant since the 1990s. It is also the only industry where success depends on the whims of a child. This book will provide a concise and in-depth introduction to the structure, practices, and market forces that impact the toy industry, including a short history, a description of the current market landscape, product trends, emerging opportunities and threats and expectations for the future. It will further cover aspects of retailing, consumer behavior, and financial markets as they relate to the industry. The primary focus is the U.S. toy industry, but one cannot ignore the global scope of the business, particularly with respect to manufacturing and opportunities for growth in emerging markets. It is intended to provide a foundation for understanding the diverse and dynamic nature of the toy industry and many things that make it unique and to provide an introduction to this fast-paced, always changing and fiercely competitive business where success is often more an art than a science.
1. A brief history of the U.S. toy industry -- 2. The toy industry by size and category -- 3. Product still rules -- 4. Buying and selling -- 5. Creating desire: licensing, advertising, and marketing -- 6. The money game: the financial realities of the toy industry -- 7. So you still want to play? -- Epilogue: play it forward: forecasting the future -- Bibliography -- Index.
Includes bibliographical references (page [149]) and index.
Title from PDF title page (viewed on February 2, 2017).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Toy industry -- United States; retailing; research; preschool; Mattel; merchandising; marketing; manufacturing; industry; Hasbro; dolls; Toy: consumption, design, development; games; Electronic books